Co-Benefits of Climate Change Mitigation Policies Literature Review and New Results - Bollen, Johannes (OECD Economics Department Working Papers, 2009)
There are local air pollution benefits from pursuing greenhouse gases emissions mitigation policies, which lower the net costs of emission reductions and thereby may strengthen the incentives to participate in a global climate change mitigation agreement. The main purpose of this paper is to assess the extent to which local air pollution co-benefits can lower the cost of climate change mitigation policies in OECD and non-OECD countries and can offer economic incentives for developing countries to participate in a post- 2012 global agreement. The paper sets out an analytical framework to answer these questions. After a literature review on the estimates of the co-benefits, new estimates, which are obtained within a general equilibrium, dynamic, multi-regional framework, are presented. The main conclusion is that the co-benefits from climate change mitigation in terms of reduced outdoor local air pollution might cover a significant part of the cost of action. Nonetheless, they alone may not provide sufficient participation incentives to large developing countries. This is partly because direct local air pollution control policies appear to be typically cheaper than indirect action via greenhouse gases emissions mitigation